Picturing a Thousand Unspoken Words: Visual Arguments and Controlling Force - Peach, Harmony (Informal Logic)

(untitled) (Informal Logic, 2021)
I explore how empathetic visual argument may be the mode best suited for eliciting appropriate force to the reasons given by arguers who face systematic identity prejudices. In the verbal mode, this force is often skewed through epistemic injustice (Fricker 2007), argumentative injustice (Bondy 2010), and discursive injustice (Kukla 2010). Highlighting their reliance on the Aristotelian sense of enthymeme, I show how visual arguments are highly context specific. Using Ian Dove’s Visual Scheming (2016) and the theory of the Retort collective (2004) via case study, I demonstrate how the visual mode can leave the appropriate force in the arguer’s control.